EGFR T790M mutation testing of non-small cell lung cancer tissue and blood samples artificially spiked with circulating cell-free tumor DNA: results of a round robin trial - Fassunke, Jana; Penzel, Roland; Volckmar, Anna-Lena; Stenzinger, Albrecht; Endris, Volker; Schirmacher, Peter (Virchows Archiv, 2017)
The European Commision (EC) recently approved osimertinib for the treatment of adult patients with locally advanced or metastatic non-small-cell lung cancer (NSCLC) harboring EGFR T790M mutations. Besides tissue-based testing, blood samples containing cell-free circulating tumor DNA (ctDNA) can be used to interrogate T790M status. Herein, we describe the conditions and results of a round robin trial (RRT) for T790M mutation testing in NSCLC tissue specimens and peripheral blood samples spiked with cell line DNA mimicking tumor-derived ctDNA. The underlying objectives of this two-staged external quality assessment (EQA) approach were (a) to evaluate the accuracy of T790M mutations testing across multiple centers and (b) to investigate if a liquid biopsy-based testing for T790M mutations in spiked blood samples is feasible in routine diagnostic. Based on a successfully completed internal phase I RRT, an open RRT for EGFR T790M mutation testing in tumor tissue and blood samples was initiated. In total, 48 pathology centers participated in the EQA. Of these, 47 (97.9%) centers submitted their analyses within the pre-defined time frame and 44 (tissue), respectively, 40 (plasma) successfully passed the test. The overall success rates in the RRT phase II were 91.7% (tissue) and 83.3% (blood), respectively. Thirty-eight out of 48 participants (79.2%) successfully passed both parts of the RRT. The RRT for blood-based EGFR testing initiated in Germany is, to the best of our knowledge, the first of his kind in Europe. In summary, our results demonstrate that blood-based genotyping for EGFR resistance mutations can be successfully integrated in routine molecular diagnostics complementing the array of molecular methods already available at pathology centers in Germany.